Factors That Influence Impulse Buying Behavior in Live Streaming E-Commerce - Siti Mariam; Tamara Syahla (Universitas Dharma Wacana, 2022)
There is a problem that many prospective customers are not sure and are hesitant to buy products that are not seen directly (through e-commerce live streaming). The customers tend not to believe in the quality of the product to be purchased and doubt the authenticity of the product even though it has been explained by influencers. The purpose of this study is to determine the factors that influence impulse buying behaviour in live streaming e-commerce. This research is a quantitative research type. The population in this study was made up of men and women aged 17-50 years in the Greater Jakarta area of 101 people who were taken using purposive sampling. Data testing was carried out using validity testing methods, reliability testing, R-Square analysis and hypothesis testing using bootstrapping by looking at the path coefficients values. Based on the research results can be drawn the following conclusions: Influencers and product quality have a positive and significant effect on customer trust; Influencers and Product Quality have a positive and significant effect on Impulse Buying Behavior; Customer trust has a positive and significant influence on Impulse Buying Behavior. There are several suggestions for this research, namely influencers can increase knowledge about the products they sell, minimize product weaknesses, increase security when shopping for live streaming, in future research they can add variables that are thought to influence impulse buying behavior such as price promotions.